Zero Divisor Graph for the Ring of Eisenstein Integers Modulo n. (15th December 2014) - Alkam, Osama; Abu Osba, Emad
Abstract : Let E n be the ring of Eisenstein integers modulo n . In this paper we study the zero divisor graph Γ ( E n ) . We find the diameters and girths for such zero divisor graphs and characterize n for which the graph Γ ( E n ) is complete, complete bipartite, bipartite, regular, Eulerian, Hamiltonian, or chordal.